CD44 in Ovarian Cancer Progression and Therapy Resistance—A Critical Role for STAT3 - Martincuks, Antons; Li, Pei-Chuan; Zhao, Qianqian; Zhang, Chunyan; Li, Yi-Jia; Yu, Hua; Rodriguez-Rodriguez, Lorna (Frontiers in Oncology, 2020)
Despite significant progress in cancer therapy over the last decades, ovarian cancer remains the most lethal gynecologic malignancy worldwide with the five-year overall survival rate less than 30% due to frequent disease recurrence and chemoresistance. CD44 is a non-kinase transmembrane receptor that has been linked to cancer metastatic progression, cancer stem cell maintenance, and chemoresistance development via multiple mechanisms across many cancers, including ovarian, and represents a promising therapeutic target for ovarian cancer treatment. Moreover, CD44-mediated signaling interacts with other well-known pro-tumorigenic pathways and oncogenes during cancer development, such as signal transducer and activator of transcription 3 (STAT3). Given that both CD44 and STAT3 are strongly implicated in the metastatic progression and chemoresistance of ovarian tumors, this review summarizes currently available evidence about functional crosstalk between CD44 and STAT3 in human malignancies with an emphasis on ovarian cancer. In addition to the role of CD44 and STAT3 interaction intrinsic in tumor cells in driving cancer progression and metastasis, we discuss how CD44 and STAT3 support the pro-tumorigenic tumor microenvironment and promote tumor angiogenesis, immunosuppression, and cancer-metabolic changes in favor of cancer progression. Finally, we review the current state of therapeutic CD44 targeting and propose superior treatment possibilities for ovarian cancer.